Single Crystalline, Non‐stoichiometric Cocrystals of Hydrogen‐Bonded Organic Frameworks. Issue 1 (2nd December 2022) - Hashimoto, Taito; Oketani, Ryusei; Nobuoka, Masaki; Seki, Shu; Hisaki, Ichiro
Abstract: Porous frameworks composed of non‐stoichiometrically mixed multicomponent molecules attract much attention from a functional viewpoint. However, their designed preparation and precise structural characterization remain challenging. Herein, we demonstrate that cocrystallization of tetrakis(4‐carboxyphenyl)hexahydropyrene and pyrene derivatives (CP‐Hp and CP‐Py, respectively) yields non‐stoichiometric mixed frameworks through networking via hydrogen bonding. The composition ratio of CP‐Hp and CP‐Py in the framework was determined by single crystalline X‐ray crystallographic analysis, indicating that the mixed frameworks were formed over a wide range of composition ratios. Furthermore, microscopic Raman spectroscopy on the single crystal indicates that the components are not uniformly distributed such as ideal solid solution, but are done gradationally or inhomogeneously. Abstract : Proof‐of‐concept non‐stoichiometric cocrystalline frameworks are formed using hexahydropyrene and pyrene derivatives with hydrogen‐bonding modules, CP‐Hp and CP‐Py . The structures and composition ratio were determined by single‐crystal X‐ray diffraction. Microscopic Raman spectroscopy on a single crystal showed that components are distributed gradationally and/or not homogeneously in the crystal.